Optimal Implantation Site of Orthodontic Micro-Screws in the Mandibular Anterior Region Based on CBCT - Wang, Yannan; Shi, Quan; Wang, Feng (Frontiers in Physiology, 2021)
Background To determine the optimal implantation site of orthodontic micro-screws based on cone beam computed tomography (CBCT) analysis in the mandibular anterior tooth region, provide a theoretical basis for orthodontic implant placement and improve post-implantation stability. Methods Forty patients who underwent CBCT scanning were selected for this study. CBCT scanning was applied to measure the interradicular distance, buccolingual dimension, labial cortical bone thickness and lingual cortical bone thickness between mandibular anterior teeth at planes 2 mm, 4 mm, 6 mm and 8 mm below the alveolar ridge crest. The data were measured and collected to obtain a comprehensive evaluation of the specific site conditions of the alveolar bone. Results The interradicular distance, buccolingual dimension and labial cortical bone thickness between the mandibular anterior teeth were positively correlated with the distance below the alveolar ridge crest (below 8 mm). The interradicular distance, buccolingual dimension, labial cortical bone thickness and lingual cortical bone thickness were all greater than those in other areas between the lateral incisor root and canine incisor root 4 mm, 6 mm, and 8 mm below the alveolar ridge crest. Conclusion The area between the lateral incisor root and the canine incisor root in planes 4 mm, 6 mm, and 8 mm from the alveolar ridge crest can be used as safe sites for implantation, while 8 mm below the alveolar ridge crest can be the optimal implantation site. An optimal implantation site can be 8 mm below the alveolar ridge crest between the lateral incisor root and the canine incisor root.